Upaya Menghindari Pelanggaran Etika Bisnis dalam Profesi Akuntan di Bank Perkreditan Rakyat Dana Nusantara Kantor Cabang Tanjungpinang - Afriyadi Afriyadi; Billy Marbiyanov; David Tan; Della Aprianingrum; Illya Firna Febriyanti; Muhammad Naufal Fitrah; Ricky Sandi Permana; Roy Mangitua Manurung; Yoma Arda Wiratama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The accounting profession in the industrial era 4.0 faces significant challenges in maintaining business ethics. In the context of Rural Credit Bank (BPR) Dana Nusantara Tanjungpinang Branch Office, efforts to avoid violations of business ethics are very important. By referring to literature studies and descriptive qualitative interviews, this research method reveals the strategies implemented by BPR Dana Nusantara Tanjungpinang in controlling ethical violations. The research results show that BPR Dana Nusantara Tanjungpinang uses internal audit and data crosscheck as the main strategy to ensure the accuracy of recording financial transactions. In addition, separation of functions and strict supervision of business processes are important steps in maintaining the integrity and honesty of company operations. However, challenges related to employee internet access present obstacles in efforts to prevent ethical violations. However, BPR Dana Nusantara Tanjungpinang continues to strive to use good vendors and implement strict operational procedures. The research results show that BPR Dana Nusantara Tanjungpinang continues to be committed to improving their internal control practices in order to create an ethical business environment and reduce the possibility of ethical violations in the future.